Paneth and Intestinal Stem Cells Preserve their Functional Integrity during Worsening of Acute Cellular Rejection in Small Bowel Transplantation - Pucci Molineris, Melisa Eliana (2017)
Graft survival after small bowel transplantation remains impaired due to acute cellular rejection (ACR), the leading cause of graft loss. Although it was shown that the number of enteroendocrine progenitor cells in intestinal crypts was reduced during mild ACR, no results of Paneth and intestinal stem cells localized at the crypt bottom have been shown so far. Therefore, we wanted to elucidate integrity and functionality of the Paneth and stem cells during different degrees of ACR, and to assess whether these cells are the primary targets of the rejection process. We compared biopsies from ITx patients with no, mild or moderate ACR by immunohistochemistry and quantitative PCR. Our results show that numbers of Paneth and stem cells remain constant in all study groups, whereas the transit-amplifying zone is the most impaired zone during ACR. We detected an unchanged level of antimicrobial peptides in Paneth cells and similar numbers of Ki-67+ IL-22R+ stem cells revealing cell functionality in moderate ACR samples. We conclude that Paneth and stem cells are not primary target cells during ACR. IL-22R+ Ki-67+ stem cells might be an interesting target cell population for protection and regeneration of the epithelial monolayer during/after a severe ACR in ITx patients.